Association Between Personal Hygiene and Nutritional Status in School-Age Children - Andromeda, Andromeda; Rafshanzany, Muhammad Luthfi; Buntoro, Joseph Dharmadi (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2023)
Malnutrition is a global health problem often found in children and adolescents. This condition can inhibit growth and development in children. Soil transmission helminth (STH) infection absorbs nutrients in the host's digestive system, affecting the host's nutritional status. One of the risk factors for STH infection is poor personal hygiene. This study aims to analyze the association of STH infections and personal hygiene with the nutritional status of elementary school children. This research is a cross-sectional study with primary data conducted in August – September 2022 on 92 children aged 6 – 12 years at Neglasari Elementary School, Cilame Village, District Bandung. Nutritional status was assessed by measuring height and weight to calculate body mass index and then putting it into the WHO 2007 Z-Score plotting curve. STH infections were determined by microscopic examination of helminth eggs from feces using the Kato-Katz method. Personal hygiene was assessed through direct interview methods. The results showed that there was no STH infection in all research respondents. The distribution of nutritional status was dominated by normal nutrition, with 66 (71.7%) respondents and the majority had implemented good personal hygiene behavior habits (78 (84.8%) respondents). It can be concluded that there was a significant relationship between personal hygiene and nutritional status in students (p= 0.000). The average score of children who had implemented good personal hygiene was in normal nutritional status.